Characteristic features of the male gender from the perspective of gіrls of mature youth from incomplete parent families (Actual Problems of Psychology in Educational Institutions, 2019)
The article presents the results of an experimental study ofgender characteristics of men, how girls, who grew up and were brought up inincomplete paternal (maternal) families, consider them in the period of matureyouth. The specificity of the attitude of girls from an incomplete family towardsmen is established. Attention is focused on classification of masculine, feminineand androgynous qualities of men in the views of respondents from incompleteand complete families. Analysis of the results of the study enabled to partiallyapproach to the reasons for the formation of ideas about the amount ofproperties and characteristics objectively typical for men in their views on girlswho were brought up in families without a father
Keywords: incomplete family; mature youth age; gender; masculinity; femininity; androgyny